Efektivitas Pembelajaran Berbasis Proyek Terhadap Hasil Belajar Materi Lingkaran Kelas VIII SMPN 1 Taliwang - Cintawan, Eny; Sridana, Nyoman; Azmi, Syahrul; Turmuzi, Muhammad (Griya Journal of Mathematics Education and Application, 2025)
This study aims to determine the effectiveness of the project-based learning model on student learning outcomes in circle material in grade VIII of SMP Negeri 1 Taliwang for the 2024/2025 school year. This type of research is a quasi experimental design with the nonequivalent posttest only control group design. The population in this study is all grade VIII students at SMP Negeri 1 Taliwang and the sample used is class VIII.4 as an experimental class and VIII.6 as a control class with the number of students in each class of 32 students selected using the cluster random sampling technique. The experimental class was treated with the application of a project-based learning model and the control class applied a conventional learning model. The research data collection technique uses test and observation techniques. The test instrument is in the form of a student learning outcome test (posttest) on circle material and observation sheets. The data analysis technique used the t-test. The results showed that there was a difference in the average learning outcomes of students who applied the project-based learning model, which was 91.2 and students who applied the conventional learning model, which was 68.2 The results showed that there was a significant difference between the learning outcomes of students in the experimental class and the control class. The average score of the students in the experimental class was higher than in the control class. Thus, project-based learning has been proven to be effective in improving students' mathematics learning outcomes on circular materials.